Taxing carbon emissions and green transition: The case of the Italian electricity market - Marco Amendola; Marco Valente (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2024)
The electricity generating sector is the single largest source of climate altering pollution. A country aiming to meet its targets for a net-zero economy needs therefore to radically reduce the emissions stemming from this sector. Charging carbon emissions is the preferred market-friendly policy to promote the diffusion of green technologies assuming that investors find more profitable to adopt technologies not burdened by the cost of carbon emissions. We study empirically the effectiveness of an increase in the cost of carbon emissions in order to favor the replacement of power plants burning fossil fuels with generators powered by renewable energy in Italy. Based on hourly data from the Italian electricity market we find that a policy increasing the cost of carbon emissions is less effective than expected in promoting clean energy investments. Indeed, increasing the cost of emissions actually increases the relative profitability of brown energy sources in respect of green ones in the most likely conditions. We conclude that increasing the cost of carbon emissions hinders the diffusion of technologies necessary for the green transition in the Italian electricity production sector. More in general, our results suggest that market friendly policies based on biasing incentives for profit-seeking operators need to carefully analyze the mechanisms underpinning the markets of interests to prevent policy failures.
Keywords: C63; H23; Q42; Q48; 330; Electricity market; Carbon pricing; Hourly-frequency model; Energy transition